Self Assembling Polymers as Polymersomes for Drug Delivery - Prakash Jain, Jay; Yenet Ayen, Wubeante; Kumar, Neeraj (Current Pharmaceutical Design, 2011)
Polymersomes are one of the most interesting and versatile architectures among various self assembled systems for drug delivery. The stability and ability to load both hydrophilic and hydrophobic molecules make them excellent candidates to use as drug delivery systems. They demand for certain physicochemical parameters; especially hydrophilic to hydrophobic block ratio of copolymer to form vesicular morphologies. Different amphiphilic copolymers as well as their architectures show differences in the requirement of hydrophilic to hydrophobic block ratio to form polymersomes with various types of morphologies. This review focuses on basic aspects of polymersomes along with a series of copolymers employed for preparation of polymersomes and their potential applications as drug delivery systems.
Keywords: ferritin (Fer)